Adolescenti, pandemia e salute mentale. Introduzione - Fagioli, Francesca; Lo Cascio, Nella; Masillo, Alice (Il sogno della farfalla, 2021)
This article introduces a monographic issue dedicated to the impact of Covid-19 pandemic on mental health with a particular attention to the world of adolescents. The objective is to review the knowledge acquired so far on the effect that the pandemic and the consequent restrictions have had on the social and private life of young generations. After discussing the most accredited studies in this field, the authors try to propose some insights in order to investigate more thoroughly what is now considered by many a real public health emergency: the sharp increase of acute psychopathological crisis, in particular depressive and self-harming, in adolescents and preadolescents from last autumn 2020.